Motivational and Behavioral Activation as an Adjunct to Psychiatric Rehabilitation for Mild to Moderate Negative Symptoms in Individuals with Schizophrenia: A Proof-of-Concept Pilot Study - Choi, Kee-Hong; Jaekal, Eunju; Lee, Ga-Young (Frontiers in Psychology, 2016)
Few psychosocial approaches address the negative symptoms of schizophrenia, which shares common features with depression and anxiety. Behavioral activation (BA) is effective for addressing depression and anxiety in adults with various mental disorders. Motivational Interviewing (MI) has been successfully applied to address ambivalence or lack of motivation towards treatment. Motivational and behavioral activation (mBA) has been developed by incorporating the core principles from BA and MI with recent findings on the negative symptoms of schizophrenia. In this study, we aimed to examine the feasibility and preliminary efficacy of mBA in a non-randomized controlled pilot study that included individuals with schizophrenia with mild to moderate negative symptoms receiving psychiatric rehabilitation. A total of 73 individuals with schizophrenia were recruited. Forty-seven of the participants who met the study inclusion and exclusion criteria were assigned to either an mBA + usual psychiatric rehabilitation group (mBA) or a usual psychiatric rehabilitation only group (treatment as usual, TAU). Administering mBA to individuals with schizophrenia with mild to moderate negative symptoms was feasible in a community mental health setting. Relative to TAU, mBA was associated with large effects in reducing negative symptoms measured using the Positive and Negative Syndrome Scale (PANSS) and the Brief Negative Symptom Scale (BNSS). However, after considering PANSS cognitive deficits and marital status as covariates due to significant differences in their baseline levels, the treatment effects on the BNSS were partially observed. In addition, participants in the mBA group showed improved verbal learning and memory compared with those in the TAU group. In individuals with schizophrenia receiving the usual forms of psychiatric rehabilitation in a community mental health setting, mBA appears to offer a promising adjunctive approach for addressing mild to moderate negative symptoms. Further investigations are needed to replicate the current findings in a randomized controlled trial.